2016
DOI: 10.4074/s0013754516004080
|View full text |Cite
|
Sign up to set email alerts
|

Le pointage dans l’autisme : Évolution de la compréhension et de la production après 6 mois d’intervention précoce

Abstract: Distribution électronique Cairn.info pour NecPlus. © NecPlus. Tous droits réservés pour tous pays. La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…On the other hand, the idea of universality can also be supported from an evolutionary perspective. Tomasello et al (2005) showed that although some non-human primates understand more about intentional action and perceptions than previously believed (and this is also true, to some extent, in children with autism, Thommen et al, 2016), only human children engage socially and culturally with others. In other words, these studies show that understanding the intentional actions and perceptions of others is not enough by itself to produce human-like social and cultural activities, it requires shared intentionality.…”
Section: Ses and Development Optimal Level For Joint Attentionmentioning
confidence: 86%
“…On the other hand, the idea of universality can also be supported from an evolutionary perspective. Tomasello et al (2005) showed that although some non-human primates understand more about intentional action and perceptions than previously believed (and this is also true, to some extent, in children with autism, Thommen et al, 2016), only human children engage socially and culturally with others. In other words, these studies show that understanding the intentional actions and perceptions of others is not enough by itself to produce human-like social and cultural activities, it requires shared intentionality.…”
Section: Ses and Development Optimal Level For Joint Attentionmentioning
confidence: 86%